Study On Various Managemental Practices On The Production Performance Of Commercial Broilers - Hegde , Ganesh (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
First hand information on production performance of commercial broilers from 108 broiler farms having a total population of 8,00,000 birds was collected by a field study. Production parameters like age and body weight at marketing, feed efficiency and liveability under different managemental practices were studied. The results indicated that average age at marketing was 48 days, body weight was 1.92 kg, feed efficiency was 2.13 and liveability was 94 per cent. The age at marketing and liveability was not affected by any of the management practices. The body weight was more in Hubbard strain of birds. Feed efficiency was more in large farms having more than 4000 birds.